RATIONALITY AND COST COMPARISON OF OUTPATIENT TYPE 2 DM THERAPY UNDER INA-CBGS: A LITERATURE REVIEW - Eka Gumilang, Nurani; Sulaeman, Agus (Universitas Muhammadiyah Ahmad Dahlan Cirebon, 2025)
This literature review evaluates the rationality of Type 2 Diabetes Mellitus (T2DM) therapy and analyzes the cost comparison between treatment expenses and Indonesian Case-Based Groups (INA-CBGs) tariffs for outpatient hospital care. The findings indicate that evidence-based therapy is essential for improving clinical effectiveness and cost efficiency. Several studies have highlighted significant discrepancies between actual outpatient treatment costs and INA-CBGs tariffs, with pharmaceutical expenses being the primary factor contributing to hospital cost deficits. A review was conducted using 11 peer-reviewed studies from 2019 to 2024, selected based on inclusion criteria such as relevance to outpatient T2DM therapy under INA-CBGs, full-text availability, and publication in Indonesian or English language. This review recommends policy adjustments to strengthen a transparent claims system, optimize an evidence-based national formulary, and enhance complication prevention strategies to improve the efficiency of DM management in Indonesia. Keywords: rationality of therapy, Type 2 Diabetes Mellitus, treatment cost, INA-CBGs, hospital, outpatient